Genetic Structure and Speciation of Zoysiagrass Ecotypes Collected in Japan. Issue 2 (1st March 2016) - Tanaka, Hidenori; Tokunaga, Risa; Muguerza, Melody; Kitazaki, Yasuo; Hashiguchi, Masatsugu; Sato, Shusei; Tabata, Satoshi; Akashi, Ryo
Abstract : Zoysia japonica Steudel, Z. matrella (L.) Merrill, and Z. pacifica (Goudswaard) M. Hotta and Kuroki [syn. Z. matrella (L.) Merr. var. pacifica Goudswaard] are native turfgrass species in Japan and are the most economically important species of this genus. Interspecific crossing within Zoysia is possible because of the similarity in chromosome number (2 n = 4 x = 40), and ecotypes with intermediate traits are found along species borders. The objectives of this study were to characterize morphological traits and determine genetic variation and population structure among 248 Zoysia accessions that we have collected throughout Japan since 1996. The accessions were classified into three species, Z. japonica, Z. matrella, and Z. pacifica . By using microsatellite markers and principal coordinate analysis (PCoA), we detected high genetic diversity among the accessions. Moreover, both PCoA and Bayesian‐based Structure analysis revealed two distinct populations represented by Z. japonica and Z. pacifica, while both ancestries were found in Z. matrella . On the basis of these results, we suggest that Z. matrella might represent an interspecific hybrid between Z. japonica and Z. pacifica ; however, further research is required to confirm this hypothesis. Differentiation among subpopulations (RST ) showed a mean value of 0.067 and a mean fixation index of individuals relative to the subpopulations (RIS ) of −0.060. This indicated moderate genetic differentiation and an excess of heterozygotes among the accessions, and probably reflected recent adaptive radiation of the species following polyploidization and hybridization in the presence of ongoing gene flow.